SOSIALISASI DAN EDUKASI PENGGUNAAN VITAMIN PADA ANAK DI KABUPATEN SINJAI - Tenri Ayu Adri; Andi Meinar Dwi Rantisari Thayeb; Luthfiyah Ambarpuri Ridwan; Andi Fitriani (Gapenas Publisher, 2023)
There has been an outbreak of the Covid-19 pandemic in Indonesia since 2022. This has really needed discipline in implementing health protocols and maintaining health to boost the immune system so that it can avoid bacteria and viruses by adopting healthy lifestyles, one example is by consuming vitamins. This community service aims to provide knowledge and information in the form of socialization and health education to participants about the use of vitamins in children. This activity was carried out at SD Negeri 91 Buluppoddo, Kec. Buluppoddo, Kab. Sinjai, South Sulawesi, where the target participants for the activity were (i) elementary school students in grades IV, V and VI. The method used in this service was an approach method in the form of lecturing, discussion, and question and answer related to the use of children's vitamins. In addition, a mini quiz was also carried out to measure the level of understanding of students (i). The results of this community service through this activity can increase the students' knowledge of SD Negeri 91 Buluppoddo about the use of children's vitamins. The enthusiasm of students really helped the course of this activity. It can be concluded that the participants understand the material explained. This can be seen from the level of understanding of the participants in the discussion sessions, questions and answers and mini quizzes